The formal seed system of maize in Ethiopia: Implications for reducing the yield gap - Kalsa, Karta K.; Semagn Kolech; Regasa, Mosisa Worku; Tsedeke Abate; Chere, Adefris Teklewold (Hindawi Limited, 2024)
Smallholder farmers' access to and use of quality seeds of improved varieties and hybrids is an integral component of sustainable maize production and the reduction of the yield gap in Ethiopia. Formal seed supply systems play a pivotal role in ensuring farmers' access to good quality seed and increasing the productivity of maize. However, the contribution of the formal seed system to the increase in the average national maize yield in the country is not well documented. This paper specifically analyzes the formal seed supply systems and contributions of improved seed to maize productivity increase in Ethiopia. Secondary sources of information, including published and unpublished data, were used. Analysis of the seed value chain from research to commercial seed producers indicated that public and private maize hybrids dominate the formal seed system. Increased use of improved seed and associated management practices has contributed to the yield increase at the national level. For every 10,000 MT of additional maize-improved seed used by smallholder farmers, the national average maize yield increased by 400 kg per hectare (R sq. = 0.59). Hence, in addition to other yield-increasing technologies and extension support, ensuring the availability of improved seed to farmers can significantly contribute to reducing the maize yield gap between the national average yield and the average yield from on-farm demonstrations already attained by farmers in Ethiopia. Various policy interventions are suggested to improve the maize seed system performance and increase the supply of maize improved seeds.